2008
DOI: 10.1111/j.1463-1326.2008.00878.x
|View full text |Cite
|
Sign up to set email alerts
|

Weight loss in obese men by caloric restriction and high‐dose diazoxide–mediated insulin suppression

Abstract: High-dose DZX-mediated insulin suppression, in combination with moderate caloric restriction and lifestyle advice, is associated with a clinically relevant degree of weight reduction. A more extensive exploration is warranted to optimize this mode of treatment and to further clarify its risks and benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 31 publications
1
25
0
Order By: Relevance
“…Short term treatments showed contradictory results with either no change in body weight (45) or anti-obesity effect in hyperinsulinemic obese adults (46). A 6-month diazoxide treatment of obese hyperinsulinemic men, combined with moderate caloric restriction, resulted in lower fasting insulin levels associated with significant weight loss, in particular of the fat mass (23). Diazoxide induces hyperglycemia, which is not observed in ␤Glud1 Ϫ/Ϫ mice possibly because, to some extent, their ␤-cells remained sensitive to glucose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Short term treatments showed contradictory results with either no change in body weight (45) or anti-obesity effect in hyperinsulinemic obese adults (46). A 6-month diazoxide treatment of obese hyperinsulinemic men, combined with moderate caloric restriction, resulted in lower fasting insulin levels associated with significant weight loss, in particular of the fat mass (23). Diazoxide induces hyperglycemia, which is not observed in ␤Glud1 Ϫ/Ϫ mice possibly because, to some extent, their ␤-cells remained sensitive to glucose.…”
Section: Discussionmentioning
confidence: 99%
“…Obese patients who received octreotide for 6 months lost weight compared with placebo (22). In a pilot study conducted on obese subjects, high dose diazoxide treatment over a 6-month period reduced their fasting insulin and fat mass (23). Thus, on a background of obesity and hyperinsulinemia, reducing the ␤-cell efficiency could favorably impact on body weight.…”
mentioning
confidence: 99%
“…However, ß-cell-targeted genetic intervention in mice protects against obesity, either by the reduction of insulin gene dosage (Mehran et al, 2012) or by the ablation of the amplifying pathway of glucose-stimulated insulin secretion (Vetterli et al, 2016a). Clinical data have shown that pharmacological inhibition of insulin secretion in obese subjects can promote weight loss (Lustig et al, 2006;van Boekel et al, 2008), although drugs used in these studies are associated with undesired side effects, such as hyperglycemia. Weight control by lifestyle modification has a low success rate, therefore calling for alternative therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Some available clinical data do support such observations made in rodents. Indeed, pharmacological inhibition of insulin secretion in obese subjects is accompanied by weight loss [20,21], although such a treatment may be associated with undesired side effects, for example hyperglycemia. Restricting the inhibition of insulin secretion to the only amplifying pathway of the b-cell might potentially prevent such side effects, as demonstrated using a genetic approach [18].…”
Section: Preventing Obesity By the Limitation Of Insulin Secretionmentioning
confidence: 99%